Anticipating Cyber Espionage: Open Source Intelligence (OSINT) Investigation and Cyber Counterintelligence - M. Yusuf Samad; Beta Kurniawati Ningtiyas; Fiqih; Fauzy Rosny; Diah Ayu Permatasari (Journal of Students‘ Research in Computer Science, 2024)
This research was conducted to analyse the use of OSINT and cyber counterintelligence in investigating cyber espionage operations using Advanced Persistent Threat (APT). Indonesia as one of the victims of cyber espionage conducted by Australia, raises the urgency of preventing cyber espionage. The purpose of this research is to answer the questions of how the utilisation of OSINT in the prevention of cyber espionage and how cyber counterintelligence can prevent cyber espionage. This research uses a qualitative method with case study on APT groups affiliated with China. The results of the analysis of cyber espionage cases conducted by I-SOON and its affiliates, which were then carried out by cyber counterintelligence efforts and investigations through OSINT with dorking techniques, can find a comprehensive picture of cyber espionage operations carried out by I-SOON, including operating practices and the underlying motivation for cyber espionage.